Development of health information materials on antimicrobial resistance with lay workers in Grahamstown/Makhanda, South Africa - Sharma, Samridhi; Srinivas, Sunitha; Tandlich, Roman (Frontiers in Public Health, 2025)
IntroductionInformation design and the design process is vital as part of the health communication strategy to tackle and prevent antimicrobial resistance. Various methods have been developed to achieve holistic tackling of antimicrobial resistance. In primary healthcare and low-resource settings, community healthcare workers and end-user participation allow for interventions to be more effective in meeting the target population’s demands and needs.MethodsDuring this study, an antimicrobial resistance health information leaflet and a trainer’s manual were designed in Makana Local Municipality’s primary healthcare settings. The developed materials were assessed for readability using seven readability formulas and suitability using the Patient Education Materials Assessment Tool and the Suitability Assessment of Materials instrument.ResultsThe health information leaflet scored a final readability of grade 14, classifying it as ‘difficult’ to read because some medical terms could not be substituted. However, due to written and verbal explanations provided, the community healthcare workers and pharmacist assistants found it easy to understand the health information leaflet and requested no further changes. The finalized health information leaflet obtained a Patient Education Materials Assessment Tool understandability score of 92%, Patient Education Materials Assessment Tool actionability score of 97%, and a Suitability Assessment of Materials instrument score of 91%, proving that it was suitable for its target population.DiscussionThe workshops and trainer’s manual resulted in a significant increase in the peer educators’ antimicrobial resistance-related knowledge. The participants felt empowered and prepared to be the change agents amongst their peers and communities because of the collaborative approach used in the study. The health information leaflet and trainer’s manual on antimicrobial resistance can come in handy for the community healthcare workers and peer educators to use as resources for future home visits and awareness raising campaigns.